Analisis Pelayanan Publik Pada Dinas Penanaman Modal Dan Pelayanan Perizinan Terpadu Satu Pintu Kabupaten Batu Bara - Ihramli Efendi; Heri Kusmanto; Isnaini Isnaini (Universitas Medan Area, 2022)
The formulation of the problem in this study is How is the service quality of the Office of Investment and One Stop Integrated Services in Batu Bara Regency in managing permits to the community?. And What are the obstacles for the Batu Bara Regency Investment and One Stop Service Office in obtaining permits to the public? The method used in this study is a qualitative research, with data collection instruments are interviews, documentation, and observation. While the data analysis used descriptive analysis. The results showed that the quality of public services at the Investment and One Stop Service Office of Batu Bara Regency refers to the theory of Parasuraman, Zeithaml, and Berry (Parasuraman, 1988), namely: public services that are in poor or unsatisfactory. In terms of reliability, the Office of Investment and One Stop Integrated Services of Batu Bara Regency is not yet classified as good. In providing service, the time is quite long. The technical team is not in place because the technical team also holds other positions. However, the physical evidence (tangibles), reliability (reability), responsiveness (responsiveness), assurance (assurance) and empathy can be said to be good. The service barrier at the Investment and One Stop Service Office of Batu Bara Regency is technological failure. Not all permits can be accessed by the public. Like building permits. In practice, it has not been implemented optimally. And limited resources. This is because the technical team is not in place, and concurrently with other positions, and is in their respective offices.